MKRN3 role in regulating pubertal onset: the state of art of functional studies - Palumbo, Stefania; Cirillo, Grazia; Aiello, Francesca; Papparella, Alfonso; Miraglia del Giudice, Emanuele; Grandone, Anna (Frontiers in Endocrinology, 2022)
Puberty is a critical process characterized by several physical and psychological changes that culminate in the achievement of sexual maturation and fertility. The onset of puberty depends on several incompletely understood mechanisms that certainly involve gonadotropin-releasing hormone (GnRH) and its effects on the pituitary gland. The role of makorin ring finger protein 3 (MKRN3) in the regulation of pubertal timing was revealed when loss-of-function mutations were identified in patients with central precocious puberty (CPP), which to date, represent the most commonly known genetic cause of this condition. The MKRN3 gene showed ubiquitous expression in tissues from a broad spectrum of species, suggesting an important cellular role. Its involvement in the initiation of puberty and endocrine functions has just begun to be studied. This review discusses some of the recent approaches developed to predict MKRN3 functions and its involvement in pubertal development.